Pengaruh Sistem Hukum Common Law Terhadap Hukum Investasi dan Pembiayaan di Indonesia (Lex Jurnalica, 2009)
World jurisdictional system subdivided as Common Law's law system and Civil Law's law system that deep its oftentimes implement impinging and interplay. Globalization has begat pranata's input sentences investment and indigenous finances system sentences Common Law goes to Indonesia that follow Civil Law's system. Its attending is trusts's institute, housings secondary finances, capital market and sekuritisasi in forms EBA that its beginning just amends on State that follow Common Law's law system have regarded investment and finances law at Indonesian one bows the neck to Civil Law's law system, where for its implement require law update because is not easily to do law adoption.Keywords: Jurisdictional System Common Law Â Investment Law, Finances Law